Digital developments : perspectives in psychology - Mihalits, Dominik Stefan; Riboli, Greta; Grgič, Regina Gregori (Unifying science, culture, and society, 2024)
"This book provides novel insights and knowledge for both psychology students as well as professionals seeking to integrate technology into their clinical or educational practices. The authors emphasize the importance of considering the behavioural and psychological implications of technology usage, both within treatment settings and in everyday life. The book is organized into five main thematic areas, each consisting of chapters written by a team of researchers who convened at the first European Conference on Digital Psychology held in Milan in 2021. Topics discussed in the book pan a wide range including e-therapy, mental health digital applications, the role of videogames in clinical psychology, virtual reality, robotics and artificial intelligence as well as today's social media. Every subchapter presents the state of the art, potential benefits and risks as well as future directions and implications concerning the usage of mentioned technologies in the field of psychology"--